2013
DOI: 10.1016/j.mgene.2013.09.003
|View full text |Cite
|
Sign up to set email alerts
|

No detectable association of IGF2BP2 and SLC30A8 genes with type 2 diabetes in the population of Hyderabad, India

Abstract: Genome-wide association studies identified novel genes associated with T2DM which have been replicated in different populations. We try to examine here if certain frequently replicated SNPs of Insulin growth factor 2 m-RNA binding protein 2 (IGF2BP2) (rs4402960, rs1470579) and Solute Carrier family 30 member 8 (SLC30A8) (rs13266634) genes, known to be implicated in insulin pathway, are associated with T2DM in the population of Hyderabad, which is considered to be a diabetic capital of India. Genotyping of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 44 publications
2
14
0
Order By: Relevance
“…Our studies showed positive association towards rs7903146 and rs13266634 polymorphisms and not in accordance with the prior studies carried out in PTDM subjects in different ethnicities (9,15,21). The associations of diabetic diseases with rs7903146 and rs13266634 polymorphisms have been carried in Indian population (14,(22)(23)(24)(25)(26)(27)(28)(29). Our results showed the positive association between rs7903146 polymorphism and T2DM (submitted for publication) and GDM (unpublished).…”
Section: Distribution Between Calcineurin Inhibitors Dosage In Ptdm Asupporting
confidence: 65%
See 2 more Smart Citations
“…Our studies showed positive association towards rs7903146 and rs13266634 polymorphisms and not in accordance with the prior studies carried out in PTDM subjects in different ethnicities (9,15,21). The associations of diabetic diseases with rs7903146 and rs13266634 polymorphisms have been carried in Indian population (14,(22)(23)(24)(25)(26)(27)(28)(29). Our results showed the positive association between rs7903146 polymorphism and T2DM (submitted for publication) and GDM (unpublished).…”
Section: Distribution Between Calcineurin Inhibitors Dosage In Ptdm Asupporting
confidence: 65%
“…synthesis, storage, and secretion (14). Previous studies showed no association of rs13266634 polymorphism with PTDM in different ethnicities (9,15,21), as well with T2DM in Indian population (25,28). Chauhan et al, (27) and our earlier study (14) showed a positive association of rs13266634 polymorphism with PTDM.…”
Section: Distribution Between Calcineurin Inhibitors Dosage In Ptdm Amentioning
confidence: 44%
See 1 more Smart Citation
“…For the rs4402960, 34 articles were available, including 49,974 cases and 54,315 controls in total. For the rs1470579, 14 articles involved 23,470 cases and 23,671 controls in total [ 12 , 15 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ] ( Table S3 ; Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…In some of these studies, this SNP (C allele) was associated with a higher risk of type-II diabetes (T2D), the MetS or its components 4, 5 , a relationship not seen in other studies 6, 7 , which explains only approximately 10% of the overall heritable risk of T2D. This contradiction among the study results and the inability of ZNT8 gene to fully explain the overall heritable risk of T2D 8 indicates the existence of a complex interaction among rs13266634 and environmental factors e.g.…”
Section: Introductionmentioning
confidence: 93%